Combining Metabolic Profiling and Gene Expression Analysis to Reveal the Biosynthesis Site and Transport of Ginkgolides in Ginkgo biloba L. - Lu, Xu; Yang, Hua; Liu, Xinguang; Shen, Qian; Wang, Ning; Qi, Lian-wen; Li, Ping (Frontiers in Plant Science, 2017)
The most unique components of Ginkgo biloba extracts are terpene lactones (TTLs) including ginkgolides and bilobalide. Study of TTLs biosynthesis has been stagnant in recent years. Metabolic profiling of 40 compounds, including TTLs, flavonoids and phenolic acids, were globally analysed in leaf, fibrous root, main root, old stem and young stem extracts of G. biloba. Most of the flavonoids were mainly distributed in the leaf and old stem. Most of phenolic acids were generally distributed among various tissues. The total content of TTLs decreased in the order of the leaf, fibrous root, main root, old stem and young stem. The TTLs were further analysed in different parts of the main root and old stem. The content of TTLs decreases in the order of the main root periderm, the main root cortex and phloem and the main root xylem. In old stems, the content of TTLs in the cortex and phloem was much higher than both the old stem periderm and xylem. The expression patterns of five key genes in the ginkgolide biosynthetic pathway were measured by real-time quantitative polymerase chain reaction (RT-Q-PCR). Combining metabolic profiling and RT-Q-PCR, the results showed that the fibrous root and main root periderm tissues were the important biosynthesis sites of ginkgolides. Based on the above results, a model of the ginkgolide biosynthesis site and transport pathway in G. biloba was proposed. In this putative model, ginkgolides are synthesized in the fibrous root and main root periderm, and these compounds are then transported through the old stem cortex and phloem to the leaves.